Incidence and mortality of women diagnosed with peripartum cardiomyopathy from 1997 to 2019 in Sweden, national registry-based study. (3rd October 2022) - Basic, C; Schaufelberger, M; Svanvik, T; Thunstrom, E
Abstract: Background: Data from previous studies indicate on increase in incidence of cardiomyopathies in Sweden. Another study confirmed high validity of diagnosis cardiomyopathy in western Sweden suggesting that a real increase in cardiomyopathy diagnosis might have occurred. Peripartum cardiomyopathy is a potentially dangerous condition that occurs few months before or up to five months after delivery. Purpose: To assess incidence and mortality rates of women diagnosed with PPCM over last two decades in Sweden. Methods: All women 18 to 50 years of age registered in the National Patient Register (NPR) in the period 1st January 1997 to 31st December 2019 were included. With the use of personal identification number (PIN), the data was than linked to other registers. Data on pregnancies were obtained from the Swedish Medical Birth Register (MBR) and data on the time of death and causes of death were gained from the Cause of Death Register. Women with PPCM were identified in the NPR using the international classification code for disease ICD-10 codes 090.3 as well as other coexisting conditions. The observation time was divided into fallowing periods: 1997–2001, 2002–2004, 2005–2007, 2008–2010, 2011–2013, 2014–2016 and 2017–2019. Results: In total, over the period of 23 years we identified 2376988 deliveries. There were 23 women diagnosed with PPCM. The prevalence of women who received the diagnostic code for PPCM increased over time from 0.003% in the first time period to 0.012% in the last time period (Figure 1). In total 4.5% of women diagnosed with PPCM died during the observation time. Conclusion: In this national, register-based study 187 women had diagnose PPCM. Total mortality over twenty years of time was low. Worryingly, we observed a four-fold increase in the use of diagnostic code for PPCM, suggesting an increse in incidence of PPCM over the last twenty-three years. More research is needed to investigate reasons for that. Funding Acknowledgement: Type of funding sources: None.